The Impact of Homoeopathy on Thyroid Health : A Case Series (Advancements in Homeopathic Research, 2024)
Objectives: The condition known as hypothyroidism  occurs when the thyroid gland does not create enough  thyroid hormone. Among women, it is the second  most prevalent endocrine condition. Radiation  therapy, thyroid surgery, and autoimmune diseases  including Hashimoto's thyroiditis are common  causes. Hypothyroidism can cause infertility,  abnormal menstruation, weight gain, changes in  cognition, and exhaustion. Thyroid stimulating  hormone is used to assess thyroid problems because  it is extremely sensitive to thyroid malfunction. The  traditional approach to treating hypothyroidism  involves monotherapy with levothyroxine. In  addition to conventional medicine, homoeopathy can  be used to treat hypothyroidism.
Keywords: Hypothyroidism; Homoeopathy; Individualized